Correlation of Sexual Maturation with Skeletal Age of Southern Chinese Girls - So Lisa L.Y (Sciendo, 1997)
The correlation of skeletal maturation with the chronological ages of the onset of f our secondary sexual characteristics (menarche, appearance of pubic hair and axillary hair, and breast development) was studied in a group of 117 Southern Chinese girls aged between 11 years, 9 months and 12 years, 3 months, who were born and brought up in Hong Kong. The skeletal maturation was assessed from left hand and wrist radiographs by the Greulich and Pyle Atlas Method (1959). The early maturers in sexual maturation were significantly more advanced in skeletal maturity with p<0.001.